2020
DOI: 10.1186/s13062-020-00275-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and iron dysregulation: distant sequence similarity between hepcidin and the novel coronavirus spike glycoprotein

Abstract: The spike glycoprotein of the SARS-CoV-2 virus, which causes COVID-19, has attracted attention for its vaccine potential and binding capacity to host cell surface receptors. Much of this research focus has centered on the ectodomain of the spike protein. The ectodomain is anchored to a transmembrane region, followed by a cytoplasmic tail. Here we report a distant sequence similarity between the cysteine-rich cytoplasmic tail of the coronavirus spike protein and the hepcidin protein that is found in humans and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 144 publications
(183 reference statements)
0
63
0
2
Order By: Relevance
“…The ectodomain is anchored to a transmembrane region, followed by a cytoplasmic tail. Recently, it was reported that a sequence similarity exists between the cysteine-rich cytoplasmic tail of the CoV spike protein with the cysteine-rich domain in hepcidin protein, which is a key regulator of iron homoeostasis in humans and other vertebrates has been reported [ 59–61 ]. SARS-CoV-2 spike (S) glycoprotein can bind DMT1 on the apical site of brush border epithelial cells in the gut mucosa, and could mediate membrane fusion and virus entry into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ectodomain is anchored to a transmembrane region, followed by a cytoplasmic tail. Recently, it was reported that a sequence similarity exists between the cysteine-rich cytoplasmic tail of the CoV spike protein with the cysteine-rich domain in hepcidin protein, which is a key regulator of iron homoeostasis in humans and other vertebrates has been reported [ 59–61 ]. SARS-CoV-2 spike (S) glycoprotein can bind DMT1 on the apical site of brush border epithelial cells in the gut mucosa, and could mediate membrane fusion and virus entry into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…20 Further in silico studies have identified that the cytoplasmic tail of the SARS-CoV-2 spike protein shares homology with hepcidin, suggesting the role that SARS-CoV-2 may play in local iron dysregulation. 21 These in silico studies need validation with larger properly designed in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical approaches, such as molecular tools [122] and protein modeling [34], provide alternative methodologies for predicting susceptible species. In particular, key residues of the ACE-2 receptor for recognizing S protein can be studied to predict potential animal hosts of SARS-CoV-2 [144][145][146]. Ultimately, an integrative framework that applies field, laboratory, and theoretical approaches provide a comprehensive framework for assessing potential hosts of SARS-CoV-2.…”
Section: Infectious Bronchitis Virus (Ibv)mentioning
confidence: 99%